MANAJEMEN LINGKUNGAN SEKOLAH SEBAGAI STRATEGI PENINGKATAN MOTIVASI BELAJAR SISWA DI SD BUDI ASIH - Rahmah, Suqya; Dianawati Wasliman, Eva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of school environmental management as a strategy to increase student learning motivation at Budi Asih Elementary School, Bandung, based on George R. Terry's management theory, which encompasses the functions of planning, organizing, actuating, and controlling. This study used a qualitative case study approach, with data collection techniques through observation, documentation, and structured interviews with the principal, teachers, and students. The results indicate that school environmental management has been implemented, but it has not been running optimally and in a structured manner. Planning is not yet written down, organization is still informal, implementation is inconsistent, and supervision is not supported by a clear evaluation and reward system. Nevertheless, a clean and comfortable school environment has a positive impact on student learning motivation. Therefore, it is necessary to strengthen the implementation of management functions systematically and sustainably.